Efektifitas Career Decision-Making Course dalam Upaya Menanggulangi Kesulitan Siswa untuk Mengambil Keputusan Karier - Yudiana, Whisnu; Dewanti, Annisa Laksmi; Suherik, Ocha Ananda; Cahyadi, Surya (MEDIAPSI, 2021)
Entering the transition period from early adolescence to late adolescence, senior high school students oftentimes experience uncertainty in determining what they should do after completing their education. This research aimed to examine the effectiveness of the Career Decision-Making Course (CDMC) as an intervention to deal with senior high school students' career decision-making difficulties. The three main categories of career decision-making difficulties investigated in this research included lack of readiness, lack of information, and inconsistency of information. Participants were 35 private high school students in the city of Bandung. The effectiveness of CDMC was tested through a pretest-posttest only design experiment. The results revealed that CDMC was effective in helping students deal with career decision-making difficulties, especially those related to lack of readiness and lack of information. However, CDMC did not significantly reduce the difficulty originating from the problem of inconsistency of information. The findings in this research imply that senior high school students should be provided with adequate information about various alternative careers that they can choose so that they are ready to determine the next step after finishing their education.Â Memasuki masa transisi dari remaja awal ke remaja akhir, siswa sekolah menengah atas seringkali mengalami kebimbangan dalam menentukan apa yang harus mereka lakukan setelah menyelesaikan pendidikan. Penelitian ini bertujuan untuk mengujikan efektivitas dari Career Decision-Making Course (CDMC) sebagai sebuah interventi untuk menangani kesulitan penentuan karier tersebut. Tiga kategori utama dalam kesulitan karier yang diteliti adalah kurangnya kesiapan, kurangnya informasi, dan inkonsistensi informasi. Partisipan adalah 35 siswa menengah atas swasta di kota Bandung. Efektivitas CDMC diuji melalui eksperimentasi pretest-posttest only design. Hasil menunjukkan bahwa CDMC efektif menangani kesulitan siswa untuk mengambil keputusan karier, terutama yang berkaitan dengan kesulitan pengambilan keputusan karena kurangnya kesiapan dan kurangnya informasi. Sementara itu, CDMC tidak berpengaruh signifikan dalam menurunkan kesulitan karena permasalahan inkonsistensi informasi. Hasil penelitian ini memberikan implikasi bahwa siswa sekolah menengah atas perlu dibekali informasi yang memadai mengenai berbagai macam alternatif karier yang bisa mereka pilih agar mereka siap menentukan langkah ke depan setelah menyelesaikan pendidikan.